Search for lepton number violating decays of D s + $$ D_{s}^{+} $$ → h − h0e+e+ - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; O. Afedulidis; X. C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; et al. (Journal of High Energy Physics)
Abstract Based on 7.33 fb −1 of e + e − collision data collected by the BESIII detector operating at the BEPCII collider at center-of-mass energies from 4.128 to 4.226 GeV, a search for the Majorana neutrino ν m is conducted in the lepton-number-violating decays of D s + $$ D_{s}^{+} $$ → h − h 0 e + e +. Here, h − represents a K − or π − , and h 0 represents a π 0, K S 0 $$ K_S^0 $$ or ϕ. No significant signal is observed, and the upper limits of their branching fractions at the 90% confidence level are determined to be B $$ \mathcal{B} $$ ( D s + $$ D_{s}^{+} $$ → ϕπ − e + e +) < 6.9 × 10 −5, B $$ \mathcal{B} $$ ( D s + $$ D_{s}^{+} $$ → ϕK − e + e +) < 9.9 × 10 −5, B $$ \mathcal{B} $$ ( D s + $$ D_{s}^{+} $$ → K S 0 $$ K_S^0 $$ π − e + e +) < 1.3 × 10 −5, B $$ \mathcal{B} $$ ( D s + $$ D_{s}^{+} $$ → K S 0 $$ K_S^0 $$ K − e + e +) < 2.9 × 10 −5, B $$ \mathcal{B} $$ ( D s + $$ D_{s}^{+} $$ → π − π 0 e + e +) < 2.9 × 10 −5 and B $$ \mathcal{B} $$ ( D s + $$ D_{s}^{+} $$ → K − π 0 e + e +) < 3.4 × 10 −5. The Majorana neutrino is searched for with different mass assumptions within the range [0.20, 0.80] GeV/c 2 in the decay of D s + $$ D_{s}^{+} $$ → ϕe + ν m with ν m → π − e +, and the upper limits of the branching fractions at the 90% confidence level are at the level of 10 −5–10 −2, depending on the mass of the Majorana neutrino.